Restless Post-War Period - Helena Ruotsala (Ethnos ry, 2022)
Kivimäki, Ville & Hytönen, Kirsi-Maria (eds.) Rauhaton rauha. Suomalaiset ja sodan päättyminen 1944–1950. Tampere: Vastapaino, 394 pp. ISBN-13: 9789517685344, ISBN-10: 9517685343.